Bioinspired membrane provides periosteum-mimetic microenvironment for accelerating vascularized bone regeneration. (January 2021) - Yang, Gaojie; Liu, Haoming; Cui, Yi; Li, Jiaqi; Zhou, Xuan; Wang, Nuoxin; Wu, Feige; Li, Yan; Liu, Yu; Jiang, Xingyu; Zhang, Shengmin
Abstract: Periosteum plays a pivotal role in vascularization, ossification and remodeling during the healing process of bone injury. However, there are few studies focused on the construction of artificial implants with periosteum-mimetic effect. To emulate the primary role of natural periosteum or endosteal tissues in bone regeneration, here we provide a functional biomimetic membrane with micropatterns of site-speciﬁc biomineralization. The micropattern is generated by using printed hydroxyapatite nanoparticles (HANPs), combined with selective growth of biomineralized apatite and in situ coprecipitation with growth factors. The biomimetic membrane can sustainably provide a periosteum-mimetic microenvironment, such as long-term topographical guidance for cell recruitment and induced cell differentiation, by releasing calcium phosphate and growth factors. We demonstrated that rat mesenchymal stem cells (rMSCs) on such biomimetic membrane exhibited highly aligned organization, leading to enhanced angiogenesis and osteogenesis. In the rat calvarial defect model, our biomimetic membranes with biomineralized micropatterns could significantly enhance vascularized ossification and accelerate new bone formation. The current work suggests that the functionally biomimetic membranes with specific biomineralized micropatterns can be a promising alternative to periosteal autografts, with great potential for bench-to-bedside translation in orthopedics.